Arthroscopic Suprapectoral and Open Subpectoral Biceps Tenodesis: A Comparison of Location, Restoration of Length-Tension and Mechanical Strength Between Techniques. Issue 7 (29th July 2014) - Werner, Brian C.; Lyons, Matthew Lawrence; Evans, Cody; Griffin, Justin W.; Hart, Joseph M.; Miller, Mark D.; Brockmeier, Stephen F.
Objectives: The approach to biceps tenodesis remains controversial, as the procedure can be performed open or arthroscopically. Little data exists directly comparing the arthroscopic suprapectoral and open subpectoral techniques, particularly in terms of location, restoration of the long head biceps length-tension relationship, and the mechanical strength of the tenodesis. The purpose of this study was to (1) determine the in-vivo tenodesis location using arthroscopic suprapectoral (ASPBT) and open subpectoral techniques (OSPBT) for long head biceps tenodesis and compare this to the location achieved in a separate clinical cohort, (2) evaluate the in-vivo restoration of the long head biceps length-tension relationship for both ASPBT and OSPBT techniques and (3) assess how location in the proximal humerus (suprapectoral or subpectoral) and method of fixation affects pull-out strength for biceps tenodesis using an interference screw implant. Our null hypothesis was that no difference existed between ASPBT and OSPBT with regards to location, restoration of the length-tension relationship, and pull-out strength. Methods: 18 matched cadaveric shoulder specimens were randomized to either open subpectoral or arthroscopic suprapectoral tenodesis groups (9 open, 9 arthroscopic.) Tenodesis was performed by two sports fellowship-trained surgeons using identical clinical techniques. Prior to surgery, a metallic bead was sutured in place, 1 cm distal to the musculotendinous junction of the long head of the biceps, and a pre-operative fluoroscopic image was obtained. Post-operatively, an additional fluoroscopic image was obtained to evaluate the location of the tenodesis and the metallic bead, which was compared to the pre-operative image to determine tensioning (Fig 1). Biomechanical testing was then performed using a MTS machine with 2.5kN load cell. Constructs were cycled for 100 cycles, then load to failure testing was performed. Results: The average tenodesis location in the ASPBT group of cadaveric specimens was 4.68 cm ± 0.97 cm distal to the top of the humerus, compared with 7.46 cm ± 1.7 cm (p < 0.0001) in the OSPBT group. This was very similar to the location observed in a separate clinical cohort. The ASPBT technique resulted in an average of 2.15 ± 0.62 cm of biceps over-tensioning compared with 0.78 ± 0.35 cm (p < 0.001) in the OSPBT group. The average load to failure in the ASPBT group was 138.8 ± 29.1 N compared to 197 ± 38.6 N (p = 0.002) in the OSPBT group. Implant pullout was significantly more frequent in the ASPBT (7/9) compared to the OSPBT (1/9) group. Conclusion: This study revealed several notable differences between the arthroscopic suprapectoral and open subpectoral biceps tenodesis techniques. The described ASPBT technique using an interference screw implant results in a more proximal tenodesis location, has the tendency to over-tension the biceps and has a significantly decreased ultimate load to failure compared with an open subpectoral technique in matched cadaver specimens. Modification of currently published arthroscopic suprapectoral techniques is necessary to improve restoration of the physiologic length-tension relationship of the biceps. Improved implants are likely necessary to achieve equivalent construct strength to the open subpectoral technique, although the clinical ramifications of this strength discrepancy have not been established.